A spatial network analysis of vegetable prices based on a partial granger causality approach - Shen, Chen; Chi, Liang; Wang, Ximeng; Han, Shuqing; Zhang, Jing; Zhu, Mengshuai (Frontiers in Physics, 2022)
The spatial difference in agricultural product prices is a crucial factor affecting the benefits of related stakeholders. This study aims to analyze the mechanisms of spatial price transmission. In this paper, taking garlic as an example, we present a vector autoregression model analyzing the reasons and relations of the price transmission between producing and selling cities. The partial Granger causality test is used to determine the direction and path of price transmission between the main producing areas and the main consuming areas. We find that the prices in different areas have a complex transmission network and fluctuate in correlation with each other. The results reveal the characteristics of agricultural product price transmission in China and provide reasons and evidence for market regulation.